Contact Angle Measurement of Melting SnAgCu Solder Paste Mix with Carbon Allotropes Using In-Line Digital Holography Technique - Mamart, Wikatsama; Somdock, Nuttakrit; Boonsri, Chantira; Plaipichit, Suwan; Buranasiri, Prathan; Kanlayasiri, Kannachai (My University, 2021)
In this research we investigated the contact angle of commercial SnAgCu solder paste mixing with some carbon allotropes such as graphite, graphene quantum dots, and fullerene of varying concentrations with melting temperature, wettability, interfacial microstructure. The wettability was assessed in terms of the contact angle. The in-line digital holography was used for determining the contact angle and morphological of samples at each temperature which the samples have been heating from room temperature until the melting temperature. In the experiment, only one beam was used as the object and reference beams which recorded by a CMOS camera. The recorded image was reconstructed by the angular spectrum digital holography numerical programing. Using the reconstructed images of our results, the shape and contact angle of solder pastes can be investigated.
Keywords: Carbon allotropes; Contact angel; Graphene; Graphene quantum dots and fullerene; In-line digital holography; Solder paste